Uracil-Induced Down-Regulation of the Yeast Uracil Permease - Séron, Karin (American Society for Microbiology, 1999)
In Saccharomyces cerevisiae the FUR4-encoded uracil permease catalyzes the first step of the pyrimidine salvage pathway. The availability of uracil has a negative regulatory effect upon its own transport. Uracil causes a decrease in the level of uracil permease, partly by decreasing the FUR4 mRNA level in a promoter-independent fashion, probably by increasing its instability. Uracil entry also triggers more rapid degradation of the existing permease by promoting high efficiency of ubiquitination of the permease that signals its internalization. A direct binding of intracellular uracil to the permease is possibly involved in this feedback regulation, as the behavior of the permease is similar in mutant cells unable to convert intracellular uracil into UMP. We used cells impaired in the ubiquitination step to show that the addition of uracil produces rapid inhibition of uracil transport. This may be the first response prior to the removal of the permease from the plasma membrane. Similar down-regulation of uracil uptake, involving several processes, was observed under adverse conditions mainly corresponding to a decrease in the cellular content of ribosomes. These results suggest that uracil of exogenous or catabolic origin down-regulates the cognate permease to prevent buildup of excess intracellular uracil-derived nucleotides.